Insulin resistance induced by hyperinsulinemia coincides with a persistent alteration at the insulin receptor tyrosine kinase domain. - Karyn J Catalano (PLoS ONE, 2014)
Insulin resistance, the diminished response of target tissues to insulin, is associated with the metabolic syndrome and a predisposition towards diabetes in a growing proportion of the worldwide population. Under insulin resistant states, the cellular response of the insulin signaling pathway is diminished and the body typically responds by increasing serum insulin concentrations to maintain insulin signaling. Some evidence indicates that the increased insulin concentration may itself further dampen insulin response. If so, insulin resistance would worsen as the level of circulating insulin increases during compensation, which could contribute to the transition of insulin resistance to more severe disease. Here, we investigated the consequences of excess insulin exposure to insulin receptor (IR) activity. Cells chronically exposed to insulin show a diminished the level of IR tyrosine and serine autophosphorylation below that observed after short-term insulin exposure. The diminished IR response did not originate with IR internalization since IR amounts at the cell membrane were similar after short- and long-term insulin incubation. Förster resonance energy transfer between fluorophores attached to the IR tyrosine kinase (TK) domain showed that a change in the TK domain occurred upon prolonged, but not short-term, insulin exposure. Even though the altered 'insulin refractory' IR TK FRET and IR autophosphorylation levels returned to baseline (non-stimulated) levels after wash-out of the original insulin stimulus, subsequent short-term exposure to insulin caused immediate re-establishment of the insulin-refractory levels. This suggests that some cell-based 'memory' of chronic hyperinsulinemic exposure acts directly at the IR. An improved understanding of that memory may help define interventions to reset the IR to full insulin responsiveness and impede the progression of insulin resistance to more severe disease states.